#TurntTrending: a systematic review of substance use portrayals on social media platforms. (8th September 2022) - Rutherford, Brienna N.; Lim, Carmen C. W.; Johnson, Benjamin; Cheng, Brandon; Chung, Jack; Huang, Sandy; Sun, Tianze; Leung, Janni; Stjepanović, Daniel; Chan, Gary C. K.
Abstract: Aims: There is a growing body of literature exploring the types of substance‐related content and their portrayals on various social media platforms. We aimed to summarize how content related to substances is portrayed on various social media platforms. Methods: This systematic review was pre‐registered on PROSPERO (ref: CRD42021291853). A comprehensive search was conducted in the databases of PubMed, Scopus, PsycINFO and Web of Science in April 2021. Original qualitative studies published post‐2004 that included thematic and sentiment analyses of social media content on tobacco, alcohol, psychostimulant, e‐cigarette, cannabis, opiate, stimulant/amphetamine, inhalant and novel psychoactive substance were included. Social media platforms were defined as online web‐ or application‐based platforms that allowed users to generate content and interact via 'liking', comment or messaging features. Only studies that included summative and/or thematic content analyses of substance‐related social media content were included. Results: A total of 73 studies, which covered 15 905 182 substance‐related posts on Twitter, YouTube, Instagram, Pinterest, TikTok and Weibo, were identified. A total of 76.3% of all substance‐related content was positive in its depiction of substance use, with 20.2% of content depicting use negatively. Sentiment regarding opiate use however was commonly negative (55.5%). Most studies identified themes relating to Health, Safety and Harms (65.0%) of substance use. Themes relating to Promotions/Advertisements (63.3%), Informative content (55.0%) and Use behaviours (43.3%) were also frequently identified. Conclusions: Substance‐related content that promotes engagement with substance use or actively depicts use appears to be widely available on social media. The large public presence of this content may have concerning influences on attitudes, behaviours and risk perceptions relating to substance use, particularly among the most vulnerable and heaviest users of social media—adolescents and young adults.